Proximal Branching of the Anterior Tibial Artery From the Popliteal Artery Increases the Risk of Vascular Injury During Total Knee Arthroplasty: A Retrospective Analysis Using Preoperative Magnetic Resonance Imaging and Intraoperative Findings - Yuya Kimura MD; Tsuneari Takahashi MD, Ph.D; Ryusuke Ae MD, Ph.D; Katsushi Takeshita MD, Ph.D (Geriatric Orthopaedic Surgery & Rehabilitation, 2022)
Introduction Arterial injury following total knee arthroplasty (TKA) can be life-threatening. There are some anatomical variations in the popliteal artery (PA) and its branches. In most cases, the PA branches into the anterior tibial artery (ATA) and posterior tibial artery (PTA), which are usually distal to the height of tibial resection in TKA. However, some cases show that the PA branches into the ATA and PTA proximal to the height of tibial resection in TKA. This study aimed to assess the distance from the posterior cortex of the proximal tibia to the anterior wall of the PA or ATA at the height of the tibial cut line, during TKA in the distal and proximal branch groups. Methods 129 patients (6 patients in the proximal branch group and 123 patients in the distal branch group) were enrolled for this study. For prediction of the distance from the posterior cortex of the proximal tibia to the anterior wall of the PA or ATA, preoperative sagittal and coronal magnetic resonance images and postoperative radiographs were evaluated. Results The distance between the posterior cortex of the proximal tibia and the anterior wall of the PA or ATA at the height of the tibial cut line was 1.8 ± 1.1 mm in the proximal branch group and 6.1 ± 2.6 mm in the distal branch group, which was significantly closer in the proximal group (P < .05). Discussion The rate of proximal branching was 4.7%. This study clarified that the proximal branching of the ATA from PA significantly decreased the distance between the posterior cortex of the proximal tibia and the anterior wall of the artery. Conclusions The proximal branch group has a high risk for arterial injury as the artery may be close to the saw, and appropriate retraction should be performed.